An Audit on Antidepressant Prescribing Practices for Children and Adolescents With Depression in Tonteg Hospital, Tonteg - Amani Hassan; Chikwado Iwudibia (BJPsych Open, 2025)
Aims: To measure the extent to which management of depression in children and adolescents compares with standard guidelines.